(untitled) (Research, Society and Development, 2020)
This article describes the technique used for maxillary sinus floor elevation with a lateral window approach, where bone grafting was used. The placement of dental implants in the posterior area of the upper jaw presents some difficulties due to the bone remaining in relation to the maxillary sinus floor. The factors that can affect are: the premature absence of permanent teeth, periodontal diseases, structure alterations of the maxillary sinus, like (hyperneumatization), which generates the need to search new options to rehabilitate and get more bone surface, allowing a correct and effective osseointegration, giving the required stability.